Design and development of an automated indoor horticulture system - Oeishee, Moslema Hoque; Shihab, Md. Nazmul Abedin; Alam, S.M.Ibnul Ul; Rayhan, S.M.Rownak (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2024.